2021
DOI: 10.12688/hrbopenres.13283.1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on clinical research: the PIPPRA and MEDRA experience

Abstract: Background: Coronavirus disease 2019 (COVID-19) has had a significant impact on clinical research. This paper aims to provide an insight into how the COVID-19 pandemic, associated public health restrictions and international guidance on the conduct of clinical research impacted two clinical rheumatology research trials - the Physiotherapist-led Intervention to Promote Physical Activity in Rheumatoid Arthritis (PIPPRA) and the MEDiterranean diet in Rheumatoid Arthritis (MEDRA) projects. Methods: The March 2019 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The MEDRA study was an open-label, telehealth-delivered, randomised controlled trial with two parallel intervention arms. In response to the pandemic and following the Irish government's announcement of a national lockdown, we sought to use telehealth methods to deliver the proposed intervention [28]. The study was designed in accordance with and adheres to the Consolidated Standards of Reporting Trials (CONSORT) statement [29].…”
Section: Methodsmentioning
confidence: 99%
“…The MEDRA study was an open-label, telehealth-delivered, randomised controlled trial with two parallel intervention arms. In response to the pandemic and following the Irish government's announcement of a national lockdown, we sought to use telehealth methods to deliver the proposed intervention [28]. The study was designed in accordance with and adheres to the Consolidated Standards of Reporting Trials (CONSORT) statement [29].…”
Section: Methodsmentioning
confidence: 99%
“…COVID-19 has had a significant impact on healthcare and clinical research, causing significant disruption to the delivery of health services and suspension of clinical research activities [ 1 ]. Clinical research stakeholders (CRS) were doubly impacted, tasked with navigating challenges across clinical and academic settings.…”
Section: Introductionmentioning
confidence: 99%
“…Impact on clinical research varied based on the stage of projects, ranging from recruitment disruptions, pausing data collection pausing and cessation [ 2 ]. Long-term effects continue to be felt across the clinical research landscape with ongoing patient concerns of COVID-19 exposure creating reluctance for clinical research participants [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The telehealth approach for delivering dietary interventions is a safe, convenient and potentially a more inclusive way to capture diverse perspectives compared to face-to-face appointments with participants which is an essential consideration given the recent Covid-19 public health pandemic [ 26 , 27 ]. A systematic review including 23 studies demonstrated that telemedicine could offer a cost-effective and widely accepted approach to deliver consultations remotely in rheumatology [ 28 ].…”
Section: Introductionmentioning
confidence: 99%